Pengaruh Komunikasi Internal dan Dukungan Sosial terhadap Kepuasan Kerja Karyawan di Koperasi Kredit Swastiastu - Diva Meilla Ni’syah; Komang Krisna Heryanda (Cattleya Darmaya Fortuna, 2026)
This study aims to analyze the influence of internal communication and social support on employee job satisfaction at Koperasi Kredit Swastiastu. Job satisfaction is an important aspect in organizational management because it can influence employee performance, motivation, and commitment to the organization. Effective internal communication and adequate social support are considered essential factors in creating a conducive work environment and improving employee satisfaction. This research employed a quantitative approach using a survey method. Data were collected from 56 employees of Koperasi Kredit Swastiastu through questionnaires. The data were analyzed using multiple linear regression analysis with the assistance of statistical software. Prior to hypothesis testing, classical assumption tests including normality, multicollinearity, and heteroscedasticity tests were conducted to ensure the validity of the regression model. The results of the study indicate that internal communication has a significant influence on employee job satisfaction. This finding suggests that the process of information exchange, clarity of instructions, and openness in communication between management and employees play an important role in shaping employees’ perceptions of their work. Furthermore, social support was found to have a positive and significant effect on job satisfaction. Employees who receive support from supervisors and colleagues tend to feel more comfortable, valued, and motivated in their work environment. The simultaneous test results also reveal that internal communication and social support together have a significant influence on employee job satisfaction at Koperasi Kredit Swastiastu. These findings imply that job satisfaction is not determined by a single factor, but rather by the interaction between effective organizational communication and supportive social relationships within the workplace. Therefore, organizations are encouraged to strengthen internal communication systems and foster a supportive work environment to enhance employee job satisfaction and organizational performance.